Regeneration of the Nervous Anam Community of the Lembak Tribe : Comparison of the Organizational Culture of the Nervous Anam Group of Lembak Panorama And Lembak Central Bengkulu - Idham Adi Wijaya; Iwan Kurniawan Subagja; Azis Hakim (Dinasti International Journal of Digital Business Management, 2026)
Regeneration of the Syaraful Anam Community of the Lembak Tribe (Comparison of Organizational Culture of the Panorama Syaraful Anam Lembak and Lembak Central Bengkulu Groups)" The problem in this research is the regeneration of the Syaraful Anam Lembak Panorama and Lembak Central Bengkulu communities. This research question is to determine the Regeneration of the Syaraful Anam Lembak Community Panorama with Lembak Central Bengkulu in an Organizational Culture Perspective. To find out about this problem. Qualitative research is applied with a descriptive approach to qualitative analysis as a method for uncovering problems. This study uses data collection techniques, namely observation, interviews, and documentation. Meanwhile, data analysis uses techniques in the form of data collection, data reduction, data presentation, and conclusion. Based on the results found in the field, the organizational culture of the two Neuronul Anam groups, namely from Lembak Panorama and Lembak Bengkulu Tengah, has many similarities in the context of organizational culture. Researchers found that the learning processes in the Pemuda Sepakat Association group in Panorama sub-district and the Nurul Ihsan group in Tengah Padang village, starting from innovation, can provide a strong example in efforts to preserve culture for further regeneration in art groups, especially Syaraful Anam. Attention to details to preserve culture, and a teacher must understand each character of the regeneration of the Young and Old Syaraful Anam groups. The orientation used and applied in the organizational culture of the Syaraful Anam group is based on the calling of the heart and concern for ancestral traditions. Team orientation is highly respected in the Syaraful Anam group because the performance requires unity